2022
DOI: 10.3390/s22093225
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Wearable Sensors for Preventing, Assessing, and Informing Recovery from Sport-Related Musculoskeletal Injuries: A Systematic Scoping Review

Abstract: Wearable technologies are often indicated as tools that can enable the in-field collection of quantitative biomechanical data, unobtrusively, for extended periods of time, and with few spatial limitations. Despite many claims about their potential for impact in the area of injury prevention and management, there seems to be little attention to grounding this potential in biomechanical research linking quantities from wearables to musculoskeletal injuries, and to assessing the readiness of these biomechanical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 256 publications
0
20
0
Order By: Relevance
“…In some studies, only one inertial sensor (placed on the trunk) was used; in others, two or three inertial sensors were used (placed on the trunk and ankles). Using different sensors with various specifications (sensors' range and sample rate differences) and different sensor placements on the body can be another reason for the variability in the reported NDA measures values [77]. An inertial sensor should be placed so that the maximum movements and signals can be captured [75,76].…”
Section: Data Collection Modality and Kinematic Variables Analysedmentioning
confidence: 99%
“…In some studies, only one inertial sensor (placed on the trunk) was used; in others, two or three inertial sensors were used (placed on the trunk and ankles). Using different sensors with various specifications (sensors' range and sample rate differences) and different sensor placements on the body can be another reason for the variability in the reported NDA measures values [77]. An inertial sensor should be placed so that the maximum movements and signals can be captured [75,76].…”
Section: Data Collection Modality and Kinematic Variables Analysedmentioning
confidence: 99%
“…IMU sensors are valid instruments which can be applied in different field‐applications such as clinical or scientific movement analysis, monitoring of activities of daily living as well as sports performance assessment. 25 , 26 , 27 Some specific examples may be the assessment of postural sway, 28 gait analysis, 29 , 30 , 31 the evaluation of jumping characteristics, 32 fall detection. 33 , 34 …”
Section: Introductionmentioning
confidence: 99%
“…IMU sensors are valid instruments which can be applied in different field-applications such as clinical or scientific movement analysis, monitoring of activities of daily living as well as sports performance assessment. [25][26][27] Some specific examples may be the assessment of postural sway, 28 gait analysis, [29][30][31] the evaluation of jumping characteristics, 32 fall detection. 33,34 Concerning upper limb kinematics, Morrow et al found an accuracy of shoulder flexion angles up to 7°during a simulated surgery compared to the gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…Based on history, physical examination and evaluation of at least one medical image obtained in the past 12 months (X-ray, CT, MRI), serious pathology of the spine will be excluded. A high Body Mass Index (BMI) could hamper the planned sensor-based movement control intervention as a result of movement artifacts ( 22 ); therefore, patients are excluded if the BMI is higher than 35 (kg/m 2 ). To avoid the risk of electromagnetic interference with the inertial sensors, patients with implanted electronic devices of any kind are excluded from this study ( 23 ).…”
Section: Methodsmentioning
confidence: 99%